2020
DOI: 10.1016/j.cgh.2019.12.025
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput, Machine Learning–Based Quantification of Steatosis, Inflammation, Ballooning, and Fibrosis in Biopsies From Patients With Nonalcoholic Fatty Liver Disease

Abstract: Background & Aims Liver biopsy is the reference standard for staging and grading nonalcoholic fatty liver disease (NAFLD), but histologic scoring systems are semiquantitative with marked interobserver and intraobserver variation. We used machine learning to develop fully automated software for quantification of steatosis, inflammation, ballooning, and fibrosis in biopsy specimens from patients with NAFLD and validated the technology in a separate group of patients. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
84
1
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 32 publications
2
84
1
5
Order By: Relevance
“…Unsurprisingly, the actual collagen content has been shown to increase exponentially, not linearly with fibrosis stage. 3 As such, the regression of 1 fibrosis stage from stage 4 to stage 3 would reflect a markedly higher anti-fibrotic effect than the regression from stage 2 to stage 1. In these cases, CPA may offer a more granular assessment, detecting small changes otherwise missed when comparing fibrosis stages.…”
Section: Nafld: Time To Apply Quantitation In Liver Biopsies As Endpomentioning
confidence: 98%
See 3 more Smart Citations
“…Unsurprisingly, the actual collagen content has been shown to increase exponentially, not linearly with fibrosis stage. 3 As such, the regression of 1 fibrosis stage from stage 4 to stage 3 would reflect a markedly higher anti-fibrotic effect than the regression from stage 2 to stage 1. In these cases, CPA may offer a more granular assessment, detecting small changes otherwise missed when comparing fibrosis stages.…”
Section: Nafld: Time To Apply Quantitation In Liver Biopsies As Endpomentioning
confidence: 98%
“…4 Specifically, we have previously demonstrated that quantitation is more sensitive than the CRN scoring system in showing changes in a subgroup of liver biopsies. 3 This finding has been particularly striking in the assessment of inflammation and ballooning, both essential features for diagnosing NASH, and for which quantitation provides more subjective results. As suchthe ability of quantitation to define key histological features as continuous variables may delineate more subtle changes associated with a trial drug in NAFLD than is currently afforded by discrete scoring systems such as NASH CRN.…”
Section: Nafld: Time To Apply Quantitation In Liver Biopsies As Endpomentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, some clinical trials currently use a reduction of fibrosis histological stage by 1 or more as an outcome; however, a reduction in stage from 4 to 3 may have different implications regarding the efficacy of an antifibrotic drug as compared to a reduction from stage 2 to 1, given that CPA increases exponentially by fibrosis stage. 70 As a caveat though, sample adequacy becomes important when dealing with such precise measurements; moreover, adequate sample size differs between etiologies of cirrhosis. 71 CPA measurement is also still subject to technical issues such as variances in staining procedure, operator experience, and imaging software used.…”
Section: Morphometric Analysismentioning
confidence: 99%